Editorial (American Journal of Islam and Society, 2004)
Have the tragic events of 9/11 resulted in a profound change in the interactionsbetween the Muslim world and the West, or has the carnage simplyaccelerated an already present trend of strained relations? It is too earlyto know, but when historians begin looking back, they will likely find evidenceto support both assertions. With the introduction of the USAPATRIOT Act, which allows the government unprecedented opportunitiesto spy on people, greatly infringing upon their civil liberties, the treatmentof the detainees at Guantanamo Bay, racial profiling, and the harassmentand deportation of Muslims residing in the country, the Bush administrationappears to be leading the “free world” into a new variant of right-wingauthoritarian government.On the other hand, the American occupation of Iraq and the Bushadministration’s plans to reshape the Middle East bear an uncanny resemblanceto a policy paper published in 1996 by an Israeli think-tank, theInstitute for Advanced Strategic and Political Studies: “A Clear Break: ANew Strategy for Securing the Realm.” Of course the symmetry betweenthe 1996 proposals (i.e., remove Saddam Hussein and weaken Syria andIran) and the current policies are no surprise, since three of the eight coauthorsnow hold key Bush administration positions: Richard Perle, memberof the Pentagon’s Defense Policy Board; Douglas Feith, undersecretaryof defense for policy; and David Wurmser, Vice President Dick Cheney’sMiddle East advisor. Thus, 9/11 has simply given the neo-conservatives anexcuse and the ability to execute what had already been envisaged. TheMiddle East, long under colonial subjugation, is re-experiencing westernaims to dominate, control, and reshape it. Thus, from a Muslim perspective,9/11 appears to have confirmed, with a vengeance, global power structuresinstead of ushering in a new era.In Covering Islam, published by the late Edward Said in 1981, Saidobserved: “For almost every Muslim, the mere assertion of an Islamicidentity becomes an act of nearly cosmic defiance and a necessity for survival(p. 72).” Though written more than 20 years ago, how more true isthis observation now? Even the simple act of naming a child (especiallyboys) is fraught with difficulties. Many of the best-loved Muslim names, ...